Sensors: Heavy Metal Sensing Using Self‐Assembled Nanoparticles at a Liquid–Liquid Interface (Advanced Optical Materials 10/2014). Issue 10 (October 2014) - Cecchini, Michael P.; Turek, Vladimir A.; Demetriadou, Angela; Britovsek, George; Welton, Tom; Kornyshev, Alexei A.; Wilton‐Ely, James D. E. T.; Edel, Joshua B.
<x xml:space="preserve">Abstract</x> The artwork represents the detection of trace metals using SERS and a self‐assembled nanoparticle film at a water/oil interface. The gold nanoparticles and mercury are shown entering the aqueous phase and assembling at the interface whilst the Raman reporter is entering from the oil phase. On page 966, J. D. E. T. Wilton‐Ely, J. B. Edel, and co‐workers use this technology to create a SERS‐based mercury sensor capable of mercury vapor detection. The artwork itself was produced by Christopher Wood. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>